Contribution à la gestion conservatoire de la zone humide de la Macta - Zair, Boualem; EL-Filali, Omar (My University, 2017)
The wetland of the Macta is a 44,500 ha site on the list of wetlands of international importance established under the Ramsar Convention in 2001. The wetland of the Macta is a depression that remains an outlet of wadis Sig, Habra and Tine which feed it generally in rainy season allowing the presence of a quasi annual moisture. According to the method of Open, the Macta Swamp is characterized by a very dry regime that extends from June to October, it is our July and August being almost absolutely dry and hot with 27.49 ° C for the August. The average temperature of the coldest month is 11.29 ° C this for the month of January. Anthropogenic impacts are increasingly heavy and represent the main factor in the degradation of the Macta marshes. Oued de Sig is considered "the main source of pollution". The Tamarix Ancient Forest has experienced a significant regression under the combined effect of climate and anthropogenic pressure. The fauna biodiversity of the wetland is threatened by the poaching of protected species, unauthorized hunting, grazing and the discharge of pollutants mainly liquidate that of industrial areas. The stagnant waters of the Macta and the surrounding vegetation forms a very favorable environment for the development and multiplication of a specific fauna which associates invertebrates, mammals, migratory birds, numerous amphibians and reptiles, and fish, such as eel (Anguilla anguilla), carp (Cyprinus carpio). The wetland is threatened by several territorial action programs which aim at a significant infra-structuring of the natural environment (for example the port of Macta) and an urban densification in the neighboring territories. Sustainable protection of this space is not easy, but it is always possible if it uses instruments that are better adapted to the real issues, if it integrates all the actors concerned by the management of the territory and if it takes charge of the environmental interactions between the ecosystems of the wetland and the entire Macta watershed.
Keywords: Ramsar Convention; degradation; infra-structuring; interactions